If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7y + 5y = -10 + 16 Combine like terms: -7y + 5y = -2y -2y = -10 + 16 Combine like terms: -10 + 16 = 6 -2y = 6 Solving -2y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-2'. y = -3 Simplifying y = -3
| 5x(2x-9)-8(2x-9)= | | 4(3x-3)=4x-4 | | 5v+1=4v-3 | | 7w=.875 | | 11-2(3p-10)=5(4-p) | | 3=-2u | | .4285714286y=-2 | | 4000=700x+500 | | 6-2=-9v+v | | 3(2n+5)=3 | | x^3-12=0 | | 20-8=-3z+9z | | 3000=400x+200 | | -9-7(8-3n)=33+7n | | 7x-x=-1-3 | | 2(5x-16)=18 | | b+1=-3-(-2) | | 2000=600x+200 | | 10(2x+1)=70 | | 1000=400*x+200 | | 4x^2-10x=0 | | 2(5x-6)=4 | | 4x^2-19x+53=9x+8 | | 9+8x=3(-10+7x) | | 9(2x+3)=81 | | x^2-11x-38=-3x-5 | | 2(4x+2)=3 | | x^2+7x-12=6 | | 6(2g+8)=8 | | 6(2g+8)= | | 99-3x=24x+15 | | 37-v=-8(-v-8) |